Low-resistivity high-failure-temperature single-layer diffusion barrier layer for copper interconnection wire

The ZrN or HfN diffusion barrier layer is prepared by magnetron sputtering process, and the process parameters are optimized to control the nitrogen content, which solves the problems of high resistivity and insufficient failure temperature of the copper interconnect diffusion barrier layer in the prior art, and achieves the effect of taking into account both low resistivity and high failure temperature.

CN119890179AActive Publication Date: 2025-04-25YUNNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510105904.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a diffusion barrier resistivity of copper interconnects below 600 degrees Celsius, while maintaining high failure temperatures.

Method used

The ZrN or HfN diffusion barrier layer is prepared by magnetron sputtering process. By optimizing process parameters such as vacuum degree, target distance, sputtering power, working gas flow rate and pressure, the nitrogen content is controlled between 18% and 25% to achieve low resistivity and high failure temperature.

Benefits of technology

A diffusion barrier layer with a resistivity of less than 10 microohms per centimeter was achieved, and a failure temperature of more than 600 degrees Celsius was maintained, significantly improving the resistivity and thermal stability of the copper interconnects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890179A_ABST
    Figure CN119890179A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of integrated circuit manufacturing, and particularly relates to a low-resistivity and high-failure-temperature single-layer diffusion barrier layer for a copper interconnection line. The diffusion barrier layer is a copper interconnection diffusion barrier layer, the copper interconnection diffusion barrier layer is located between copper and a silicon substrate, the copper interconnection diffusion barrier layer contains M and N elements at the same time, M is selected from one of Zr and Hf, the copper interconnection diffusion barrier layer is prepared through a magnetron sputtering technology, and when the copper interconnection diffusion barrier layer is prepared through magnetron sputtering, the thickness of the copper interconnection diffusion barrier layer is smaller than that of the N; and the nitrogen content accounts for 18-25% of the working gas content. According to the method, the ultrathin single-layer nitride diffusion barrier layer with the resistivity lower than 40 microohms per centimeter (even lower than 10 microohms per centimeter) at the temperature of 600 DEG C and the failure temperature higher than 600 DEG C is obtained for the first time through magnetron sputtering. The composition is reasonable in design, the process is simple and controllable, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of integrated circuit manufacturing, and in particular relates to a single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnection lines. Background Art

[0002] The structure of metal zirconium is hcp (α phase), which transforms into body-centered cubic bcc structure (β phase) at a high temperature of 1135K. (α-Zr) has a smaller work function (4.15eV) than metal Ti, a higher melting point (2128K), and a lower resistivity (3.86×10 – 5 W cm 2 ), many advantages have been frequently applied to silicon-based microelectronic devices and power electronic devices [62-64] Compared with the commonly used TiN and TaN diffusion barrier materials, ZrN has lower resistance and higher heat generation (-87.33 kcal / mol), which is higher than TiN (-80.4 kcal / mol) and TaN (-60.3 kcal / mol). High heat generation means better thermal stability. These advantages of the film also reflect the great advantages of being a diffusion barrier material.

[65] TAKEYAMA MB research proved that the barrier layer of 100nm nanocrystalline ZrN (Cu / ZrN / Si) will not undergo structural changes at a high temperature of 800℃. When the thickness of the ZrN barrier layer is reduced to 20nm, there is no solid phase reaction and significant structural changes at temperatures up to 600℃ or higher. Sato et al. proved that the 5nm thick ZrN film has a high temperature of 1.33×10 -5 Pa vacuum can withstand high temperature annealing of 500℃ without copper diffusion; Cheng-Shi Chen and other researchers prepared two ZrN films with different preferred orientations by changing the substrate temperature, and studied the diffusion barrier performance of ZrN films in Cu / ZrN / Si system with the change of texture coefficient and film thickness, and concluded that the diffusion distance of Cu depends on the orientation and thickness of ZrN film, which can be explained by atomic structure, morphology and total area of ​​grain boundaries. It is proved that ZrN film with a thickness of 120nm and a texture coefficient of 0.27 has both good resistivity and a Cu diffusion barrier temperature of up to 800℃. On the other hand, 70nm thick ZrN film can still remain stable at 700℃; YingWang et al. proved that the 15nm Zr-Ti-N barrier layer prepared by adding Ti element to ZrN can still play a barrier role to prevent the diffusion of copper at a high temperature of 700℃; Jian-LongRuan et al. prepared an ultra-thin ZrN (10nm) diffusion barrier layer by DC reactive magnetron sputtering under different negative substrate biases and acted as a barrier for Cu and SiO at temperatures as high as 800℃. 2The diffusion barrier between the two layers can also maintain the feasibility for 30 minutes; Y. Menga and other researchers prepared a 5 nm amorphous Zr-BN film by reactive magnetron sputtering, which showed good thermal stability and barrier performance below 650 ° C. In the future, as the feature size of integrated circuits is getting smaller and smaller and the thickness of interconnection barrier layers is pursuing ultra-thin, the research on Zr-based metal barrier layers is of great significance. Woo-Cheol ROH and other researchers deposited a 100 nm thick Hf (C, N) film on a silicon substrate by pulsed DC plasma enhanced metal organic chemical vapor deposition, which can well prevent Cu from diffusing into silicon at up to 600 ° C; Ken-ichi YOSHIMOTO and other researchers

[79] Thin films prepared by sputtering, Cu / Hf(250nm) / Si, Cu / CuHf 2 The failure temperatures of Cu(150nm) / Hf(100nm) / Si and Cu / HfN(100nm) / Hf(150nm) / Si are below 480℃, below 480℃, and above 630℃, respectively. After annealing at 600℃, Cu / Hf(50nm) / Si prepared by Keng-LiangOu by magnetron sputtering forms Cu in the copper-diffused silicon. 3 Cu / HfN in Si 0.47 The (50nm) / Si contact system can be annealed at 650℃ for 30 minutes without any reaction. Due to the accelerated diffusion of Cu through the crystalline Hf-N barrier layer, Cu was observed after annealing at 700℃. 3 Si compounds.

[0003] However, a search revealed that there are few reports on technologies for ultra-thin nitride diffusion barrier layers that can achieve a resistivity of less than 40 microohms per centimeter (or even less than 10 microohms per centimeter) at 600 degrees Celsius and a failure temperature greater than 600 degrees Celsius. Summary of the invention

[0004] The present invention takes the elements after the fifth period of the fourth subgroup as the research object, and for the first time uses magnetron sputtering to prepare a diffusion barrier layer with a resistivity of less than 40 micro-ohms per centimeter at 600 degrees Celsius.

[0005] After optimization, the present invention can prepare a diffusion barrier layer with a resistivity of less than 10 micro-ohms per centimeter at 600 degrees Celsius and a failure temperature greater than 600 degrees Celsius.

[0006] The present invention discloses a single-layer diffusion barrier layer with low resistivity and high failure temperature for a copper interconnect line. The diffusion barrier layer is a copper interconnect diffusion barrier layer, the copper interconnect diffusion barrier layer is located between copper and a silicon substrate, the copper interconnect diffusion barrier layer contains both M and N elements, the M is selected from one of Zr and Hf, the copper interconnect diffusion barrier layer is prepared by a magnetron sputtering process, and when the copper interconnect diffusion barrier layer is prepared by magnetron sputtering, the nitrogen content accounts for 18% to 25% of the working gas content.

[0007] The present invention provides a single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects. When the ZrN diffusion barrier layer is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~15×10 -4 Pa, preferably 1.8~2.5×10 -4 Pa, more preferably 2×10 -4 Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 60-150 W, preferably 80-120 W, and more preferably 100 W; The working gas flow rate is 20-30 sccm, preferably 22-28 sccm, and more preferably 25 sccm; The working pressure is 0.6~0.8Pa, preferably 0.65~0.75Pa, and more preferably 0.7Pa; The target material is a Zr target material with a purity greater than or equal to 99.95%; The working gas is composed of argon and nitrogen, wherein the nitrogen content accounts for 18% to 22% of the working gas content, and more preferably 20%; The temperature of the substrate is 20~25℃.

[0008] Preferably, when the ZrN diffusion barrier layer is prepared by magnetron sputtering, the volume ratio of argon and nitrogen in the working gas is 20:5, that is, the flow rate of argon is 20 sccm and the flow rate of nitrogen is 5 sccm. At this time, the sputtering power is preferably 100W.

[0009] The roughness of the obtained ZrN diffusion barrier layer is 0.98 nm; After heat treatment at 600°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 7.31 μΩ.cm.

[0010] After heat treatment at 700°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 20.2 μΩ.cm.

[0011] The present invention provides a single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects. When the HfN diffusion barrier layer is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~15×10-4Pa, preferably 1.8~6.2×10-4Pa, and more preferably 5×10-4Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 50-120 W, preferably 70-100 W, and more preferably 80 W; The working gas flow rate is 18-30 sccm, preferably 19-28 sccm, and more preferably 25 sccm; The working pressure is 0.6~0.8Pa, preferably 0.65~0.75Pa, and more preferably 0.7Pa; The target material is a Hf target material with a purity greater than or equal to 99.95%; The working gas is composed of argon and nitrogen, wherein the nitrogen content accounts for 18% to 22% of the working gas content, and more preferably 20%; The temperature of the substrate is 20~25℃.

[0012] Preferably, when the HfN diffusion barrier layer is prepared by magnetron sputtering, the volume ratio of argon and nitrogen in the working gas is 20:5, that is, the flow rate of argon is 25 sccm and the flow rate of nitrogen is 5 sccm. At this time, the sputtering power is preferably 80W.

[0013] The roughness of the obtained HfN diffusion barrier layer is 0.954 nm. Before heat treatment, the resistivity of the HfN diffusion barrier layer is 38.2 μΩ.cm After heat treatment at 600°C for 30 min, the resistivity of the obtained HfN diffusion barrier layer is 9.9 μΩ.cm.

[0014] After heat treatment at 700°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 96 μΩ.cm.

[0015] The diffusion barrier layer obtained by the present invention has a resistivity lower than 10 micro-ohms per centimeter after heat treatment at 600 degrees Celsius, and its failure temperature can be greater than 600 degrees Celsius.

[0016] After optimization, the resistivity of the obtained diffusion barrier layer is less than 8 microohms per centimeter after heat treatment at 600 degrees Celsius, and its failure temperature can be greater than 650 degrees Celsius. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the surface morphology of the ZrN diffusion barrier layer prepared in Example 1 of the present invention.

[0018] Figure 2 This is the surface morphology of the HfN diffusion barrier layer prepared in Example 2 of the present invention.

[0019] Figure 3 XRD spectra of the ZrN diffusion barrier layer prepared in Example 1 of the present invention in the deposited state and after annealing.

[0020] Figure 4 XRD spectra of the HfN diffusion barrier layer prepared in Example 2 of the present invention in the deposited state and after annealing.

[0021] Figure 5 The resistivity change curves of the ZrN diffusion barrier layer prepared in Example 1 of the present invention in the deposited state and after annealing.

[0022] Figure 6 The resistivity change curves of the HfN diffusion barrier layer prepared in Example 2 of the present invention in the deposited state and after annealing.

[0023] Figure 7 The XRD spectra of the diffusion barrier layer obtained in Comparative Example 1 as deposited and after annealing.

[0024] Figure 8 Resistivity change diagram of the diffusion barrier layer before heat treatment obtained to explore case series 1.

[0025] Fig. 9 The XRD spectra of the diffusion barrier layer obtained in Comparative Example 2 as deposited and after annealing.

[0026] Fig.10 Resistivity change diagram of the diffusion barrier layer before heat treatment obtained to explore case series 2. DETAILED DESCRIPTION

[0027] In the embodiments and comparative examples of the present invention, a ZrN layer, an HfN layer barrier film and a 180 nm copper layer simulating a Cu interconnection layer are prepared on an N-type single crystal silicon (100) substrate. The resistivity of N-type single crystal silicon (100) substrate is 0.05-0.1Ω.CM; The purity of the target material used is greater than 99.95%, and the purity of the argon and nitrogen used is 5N grade or above.

[0028] The main equipment used are SB-5200DTD ultrasonic cleaner, TRP-450 magnetron sputtering coater and SLG1000-60 tube furnace.

[0029] Pre-treatment: First, the silicon wafer was ultrasonically cleaned in acetone solution for 10 minutes to remove organic pollutants on the surface of the silicon wafer. After taking it out, it was rinsed with deionized water and dried with nitrogen. Then, the silicon wafer was ultrasonically cleaned in anhydrous ethanol for 5 minutes to remove grease on the substrate surface and ensure that the film adheres better to the silicon substrate. After taking it out, it was rinsed with deionized water and dried with nitrogen. Then, the silicon wafer was immersed in 5% HF solution for 2 minutes to remove the surface oxide layer. The silicon oxide (SiO 2 ) layer will hinder the deposition of the film and cause poor uniformity. After taking it out, rinse it with deionized water and blow it dry with nitrogen. Finally, put it into anhydrous ethanol for ultrasonic cleaning for 5 minutes, take it out and blow it dry with nitrogen for later use.

[0030] When depositing the copper layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16 cm, sputtering power is 100 W, working gas flow rate is 20 sccm, working pressure is 0.7 Pa. The target material used is a Cu target material with a purity greater than or equal to 99.95%; the working gas used is composed of argon gas, wherein the flow rate of argon gas is 20 sccm; the temperature of the substrate is 25°C.

[0031] Example 1 On a spare N-type single crystal silicon (100) substrate, a zirconium nitride layer is deposited by magnetron sputtering, and then a copper layer with a thickness of 180 nm is deposited to obtain a Cu (180 nm) / ZrN (10 nm) / Si deposited sample; when depositing the ZrN layer, the following control is performed: Background vacuum degree 2×10 -4 Pa, target distance is 16cm, sputtering power is 100W, working gas flow rate is 25sccm, working pressure is 0.7Pa. The target used is Zr target with purity greater than or equal to 99.95%; the working gas used is composed of argon and nitrogen, where the flow rate of argon is 20sccm and the flow rate of nitrogen is 5sccm; the temperature of the substrate is 25℃. Sputtering for 30min.

[0032] like Figure 1 The surface morphology of the deposited barrier layer is shown, and the layer is continuous, dense and has no cracks.

[0033] Failure temperature test experiment: The annealing test was carried out at 500℃-700℃ in nitrogen atmosphere (test time 30min). The XRD characteristics of the obtained product before and after annealing are shown in Figure 3 ; The resistivity changes after annealing at different temperatures are shown in Figure 5 ,Depend on Figure 3 , 5It can be seen that the diffusion barrier aging temperature of the Cu (180 nm) / ZrN (10 nm) / Si deposited sample prepared in Example 1 is about 700°C.

[0034] The roughness of the obtained ZrN diffusion barrier layer is 0.98 nm and the resistivity is 35.2 μΩ.cm. After heat treatment at 600°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 7.31 μΩ.cm.

[0035] After heat treatment at 700°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 20.2 μΩ.cm.

[0036] Explore Case Series 1 Other conditions are the same as those in Example 1, except that: The working gas flow rate is 25 sccm, and the flow rate of nitrogen accounts for 20%, 30%, and 40% of the working gas flow rate; The resistivity of the obtained products is 3.52×10 -5 Ω∙cm、5.23×10 -5 Ω∙cm、14.4×10 -5 Ω∙cm, such as Figure 8 As the nitrogen partial pressure increases, the resistivity of the film generally shows a gradual upward trend.

[0037] Comparative Example 1 The other conditions are the same as those in Example 1, except that the working gas is argon. The XRD spectra of the obtained diffusion barrier layer as deposited and after annealing are shown in Figure 7 .from Figure 7 It can be seen that the aging temperature of the obtained diffusion barrier is about 600°C.

[0038] Example 2 On a spare N-type single crystal silicon (100) substrate, a hafnium nitride layer is deposited by magnetron sputtering, and then a 180nm thick copper layer is deposited to obtain a Cu (180nm) / HfN (10nm) / Si deposited sample; when depositing the HfN layer, control: Background vacuum degree 2×10 -4 Pa, target distance is 16cm, sputtering power is 80W, working gas flow rate is 25sccm, working pressure is 0.7Pa. The target used is Hf target with purity greater than or equal to 99.95%; the working gas used is composed of argon and nitrogen, where the flow rate of argon is 20sccm and the flow rate of nitrogen is 5sccm; the temperature of the substrate is 25℃. Sputtering for 30min.

[0039] like Figure 2The surface morphology of the deposited barrier layer is shown, and the layer is continuous, dense and has no cracks.

[0040] Failure temperature test experiment: The annealing test was carried out at 500℃-700℃ in nitrogen atmosphere (test time 30min). The XRD characteristics of the obtained product before and after annealing are shown in Figure 4 ; The resistivity changes after annealing at different temperatures are shown in Figure 6 ,Depend on Figure 4 , 6 It can be seen that the aging temperature of the diffusion barrier of the Cu (180 nm) / HfN (10 nm) / Si deposited sample prepared in Example 2 is about 600-650°C.

[0041] The roughness of the obtained HfN diffusion barrier layer is 0.954 nm. Before heat treatment, the resistivity of the HfN diffusion barrier layer is 38.2 μΩ.cm After heat treatment at 600°C for 30 min, the resistivity of the obtained HfN diffusion barrier layer is 9.9 μΩ.cm.

[0042] After heat treatment at 700°C for 30 min, the resistivity of the obtained HfN diffusion barrier layer is 96 μΩ.cm.

[0043] Comparative Example 2 The other conditions are the same as those in Example 2, except that the working gas is argon. The XRD spectra of the obtained diffusion barrier layer as deposited and after annealing are shown in Fig. 9 .from Fig. 9 It can be seen that the aging temperature of the obtained diffusion barrier is about 550°C.

[0044] Explore Case Series 2 Other conditions are the same as those in Example 2, except that: The working gas flow rate is 25 sccm, and the flow rate of nitrogen accounts for 20%, 30%, and 40% of the working gas flow rate; The resistivity of the obtained product is shown in Fig.10 .

Claims

1. A single-layer diffusion barrier with low resistivity and high failure temperature for copper interconnects, characterized in that: The diffusion barrier layer is a copper interconnect diffusion barrier layer, the copper interconnect diffusion barrier layer is located between copper and a silicon substrate, the copper interconnect diffusion barrier layer contains both M and N elements, the M is selected from one of Zr and Hf, and the copper interconnect diffusion barrier layer is prepared by a magnetron sputtering process. When the copper interconnect diffusion barrier layer is prepared by magnetron sputtering, the nitrogen content accounts for 18% to 25% of the working gas content.

2. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 1, characterized in that: When the ZrN diffusion barrier layer is prepared by magnetron sputtering, control: The background vacuum degree is 1~15×10 -4 Pa, preferably 1.8~2.5×10 -4 Pa, more preferably 2×10 -4 Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 60-150 W, preferably 80-120 W, and more preferably 100 W; The working gas flow rate is 20-30 sccm, preferably 22-28 sccm, and more preferably 25 sccm; The working pressure is 0.6~0.8Pa, preferably 0.65~0.75Pa, and more preferably 0.7Pa; The target material is a Zr target material with a purity greater than or equal to 99.95%; The working gas is composed of argon and nitrogen, wherein the nitrogen content accounts for 18% to 22% of the working gas content, and more preferably 20%; The temperature of the substrate is 20~25℃.

3. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 2, characterized in that: When the ZrN diffusion barrier layer is prepared by magnetron sputtering, the volume ratio of argon and nitrogen in the working gas is 20:5, that is, the flow rate of argon is 20 sccm and the flow rate of nitrogen is 5 sccm. At this time, the sputtering power is preferably 100W.

4. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 1, characterized in that: The roughness of the obtained ZrN diffusion barrier layer is 0.98 nm; After heat treatment at 600 °C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer was 7.31 μΩ.cm; After heat treatment at 700°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 20.2 μΩ.cm.

5. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 1, characterized in that: When the HfN diffusion barrier layer is prepared by magnetron sputtering, control: The background vacuum degree is 1~15×10-4Pa, preferably 1.8~6.2×10-4Pa, and more preferably 5×10-4Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 50-120 W, preferably 70-100 W, and more preferably 80 W; The working gas flow rate is 18-30 sccm, preferably 19-28 sccm, and more preferably 25 sccm; The working pressure is 0.6~0.8Pa, preferably 0.65~0.75Pa, and more preferably 0.7Pa; The target material is a Hf target material with a purity greater than or equal to 99.95%; The working gas is composed of argon and nitrogen, wherein the nitrogen content accounts for 18% to 22% of the working gas content, and more preferably 20%; The temperature of the substrate is 20~25℃.

6. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 5, characterized in that: When the HfN diffusion barrier layer is prepared by magnetron sputtering, the volume ratio of argon and nitrogen in the working gas is 20:5, that is, the flow rate of argon is 25 sccm and the flow rate of nitrogen is 5 sccm. At this time, the sputtering power is preferably 80W.

7. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 5, characterized in that: The roughness of the obtained HfN diffusion barrier layer is 0.954 nm; Before heat treatment, the resistivity of the HfN diffusion barrier layer was 38.2 μΩ.cm; After heat treatment at 600 °C for 30 min, the resistivity of the obtained HfN diffusion barrier layer was 9.9 μΩ.cm; After heat treatment at 700°C for 30 min, the resistivity of the obtained ZrN diffusion barrier layer is 96 μΩ.cm.

8. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 5, characterized in that: The resistivity of the obtained diffusion barrier layer is lower than 10 micro-ohms per centimeter after heat treatment at 600 degrees Celsius, and its failure temperature can be greater than 600 degrees Celsius.

9. The single-layer diffusion barrier layer with low resistivity and high failure temperature for copper interconnects according to claim 8, characterized in that: The resistivity of the obtained diffusion barrier layer is lower than 8 micro-ohms per centimeter after heat treatment at 600 degrees Celsius, and its failure temperature can be greater than 650 degrees Celsius.

Citation Information

Patent Citations

  • Nano ULSI-Cu wiring HfSiN diffusion impervious layer thin film and preparation process

    CN101969067A

  • Method for preparing ZrN (100) single-orientation zirconium nitride film by MOCVD (Metal Organic Chemical Vapor Deposition) on Si (111) substrate

    CN118064978A

  • Method of forming an FeRAM capacitor having a bottom electrode diffusion barrier

    US20030129771A1

  • Process for producing thin hafnium or zirconium nitride coatings

    US20070042224A1